Social Representation of Insecurity among Young Ecuadorian University Students: the Ambato Case - Molina Coloma, Verónica; Reyes Sosa, Hiram; Larrañaga Egilegor, Maider (Pensando Psicología, 2015)
Introduction: Insecurity is a matter for social concern in Ecuador, as well as in many Latin American countries. References to events associated with insecurity are habitual in the communications media and reflect the situation of uncertainty experienced by the population on a daily basis. Objective: An analysis is proposed of the social representation of insecurity. The aim is thus to determine how young people conceive of and explain this social object. Methodology: Information was gathered using qualitative techniques. 271 young university students took part in the study (67% women and 33% men), with a median age of 21.32 (dt: 2.23). Results: Analysis of the central nucleus and peripheral system showed that young people perceive an insecure context characterized by uncertainty and fear of going out to public places or specific zones. This feeling of insecurity is further heightened by the lack of mechanisms to regulate this negative climate, such as the inefficient structure of judicial institutions. In relation to gender differences, it was found that women report experiencing greater fear and vulnerability in their daily lives than men. Conclusions: In Ambato, strategies have been developed to reduce insecurity; however, these mechanisms have not helped to decrease the perception of fear established in the context.